Literasi Zakat, Infaq, dan Sedekah melalui Pendekatan Akuntansi pada Masyarakat Bentiring Permai Bengkulu - Indah Oktari Wijayanti; Herawansyah Herawansyah; Nikmah Nikmah; Novita Sari (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to improve literacy on zakat, infaq, and almsgiving through an accounting approach among the community of Bentiring Permai, Bengkulu City. The main problem faced by the community is the lack of understanding regarding zakat calculation and the absence of systematic financial recording in managing religious social funds. The method used is an educational and participatory approach through interactive lectures, zakat calculation practices, and simple financial recording simulations referring to PSAK 109. This activity involved 50 participants consisting of the general public, mosque administrators, and small business actors, and was conducted at the Bentiring Permai Village Hall. The results show a significant increase in participants’ understanding, as indicated by the comparison of pre-test and post-test results, as well as improved ability in calculating zakat and conducting simple financial recording. In addition, this activity increased public awareness of the importance of transparency and accountability in managing zakat, infaq, and almsgiving funds. Therefore, this program is expected to contribute to improving the quality of accounting-based management of religious social funds within the community.